Analytical Solutions for Systems of Singular Partial Differential-Algebraic Equations. (23rd February 2015) - Filobello-Nino, U.; Vazquez-Leal, H.; Benhammouda, B.; Perez-Sesma, A.; Jimenez-Fernandez, V. M.; Cervantes-Perez, J.; Sarmiento-Reyes, A.; Huerta-Chua, J.; Morales-Mendoza, L. J.; Gonzalez-Lee, M.; Diaz-Sanchez, A.; Pereyra-Díaz, D.; et al.
Abstract : This paper proposes power series method (PSM) in order to find solutions for singular partial differential-algebraic equations (SPDAEs). We will solve three examples to show that PSM method can be used to search for analytical solutions of SPDAEs. What is more, we will see that, in some cases, Padé posttreatment, besides enlarging the domain of convergence, may be employed in order to get the exact solution from the truncated series solutions of PSM.